Cocktail vaccine for the management of Hyalomma anatolicum and Rhipicephalus microplus - Manjunathachar, Haranahally Vasanthachar; Kumar, Binod; Parthasarathi, Balasamudram Chandrasekhar; Chigure, Gajanan M.; Saravanan, Buddhi Chandrasekaran; Sankar, Muthu; Harish, Darasaguppe Ramachandra; de la Fuente, José; Ghosh, Srikanta (Frontiers in Immunology, 2024)
IntroductionGlobally, ticks rank second only to mosquitoes as vectors of deadly pathogens affecting humans and first in transmitting animal pathogens, presenting a significant challenge to human wellness and sustainability of livestock-based industries. Traditional tick control via chemical acaricides impacts on the environment and has led to the emergence of multi-acaricide-resistant tick populations. Use of immunoprophylactic, along with other components of integrated tick management, holds the potential to mitigate tick infestations in a sustainable manner. To control multi-species tick infestations, the concept of a cocktail vaccine comprising of more than one antigens has emerged as a viable solution due to the inconsistent efficacy of single antigen-based immunization protocol.MethodsIn this study, a dual antigen cocktail immunization protocol was developed targeting ferritin2 (FER2) and tropomyosin (TPM) proteins, which are associated with ticks’ essential cellular and physiological functions, like blood iron homeostasis and muscle contractions.ResultsDual gene silencing of FER2 and TPM genes in Hyalomma anatolicum resulted in a 75.3% reduction in infested ticks, a 95.4% decrease in egg masses, and a complete loss of egg hatching when compared to control ticks. Microscopically, an altered ovarian cellular architecture, marked by vacuolation and reduced nucleus-to-cytoplasmic ratio were noted in the gene knocked down ticks. An immunization with cocktails of 300 µg dose of each protein, rHaFER2 and rHaTPM was standardized in a rat model and was used to immunize cross-bred (Bos indicus x B. taurus) male cattle with Montanide ISA 50V2 adjuvant on days 0, 28, and 49. A significant (p < 0.001) IgG and IgG2 antibody response was observed in the immunized animals with high IgG levels sustained until day 119 post-primary immunization, showing a 4.1-fold increase over the pre-immunization period. The animals were challenged with larvae and adults of H. anatolicum and larvae of Rhipicephalus microplus. Immunization with the cocktail antigen resulted an efficacy of 70% and 76% against H. anatolicum larvae and adults, respectively, and 54% against R. microplus infestations. Compared to single-antigen immunization, the immunization with cocktail antigens demonstrated higher protection against R. microplus and H. anatolicum ticks. The results advance the development of cocktail vaccines to control multiple tick species.